Russian Lawyers and the Soviet State - Eugene Huskey (Princeton University Press, 2014)
This is a study of conflict between pre- and postrevolutionary visions of the role of law and the professions in Russia. It seeks to explain how the Bar, a legal institution of the old order dedicated to the representation of individual interests, has been integrated into the Soviet state, whose proclaimed commitment is to the furtherance of collective, or class, interests. The primary focus of the work is on the first two decades of Soviet rule, from the formal abolition of the Russian Bar in 1917 to the end of the 1930s when private legal practice was finally outlawed, when large numbers of young Soviet-trained advocates entered the profession, and when the last vestiges of overt resistance to party and government control of the Bar were eliminated. It was in this period that the Soviet Bar acquired its definitive shape and the major issues of professional development were resolved